Celiac disease in first degree relatives of celiac children - Oliveira,Andreia (2012)
CONTEXT - The first degree relatives of celiac patients represent a high risk group for the development of this disorder, so their screening may be crucial in the prevention of long-term complications. OBJECTIVE - In order to determine the prevalence of celiac disease in a group of first degree relatives of children with proven gluten intolerance, we conducted a prospective study that consisted in the screening of celiac disease, using a capillary immunoassay rapid test that allows a qualitative detection of IgA antibody to human recombinant tissue transglutaminase (IgA-TTG). METHODS - When the screening test was positive subjects were advised to proceed with further investigation. The screening test was performed in 268 first degree relatives (143 mothers, 89 fathers, 36 siblings) corresponding to 163 children with celiac disease. RESULTS - Screening test was positive in 12 relatives (4.5%), of which 1 refused to continue the investigation. In the remaining 11 relatives celiac disease was diagnosed in 7 cases (2.6%, 5 mothers, 2 fathers) who had a median age of 39 years (27-56 years), mild gastrointestinal symptoms, high titre of IgA-TTG and histology abnormalities confirming the diagnosis. All these patients are currently on a gluten-free diet. CONCLUSION - The prevalence of celiac disease among first degree relatives (2.6%) was 5 times higher than that in the general population. Although the recommendations for screening asymptomatic high risk groups, such as first degree relatives, are not unanimous the early diagnosis is crucial in preventing complications, including nutritional deficiency and cancer.